Queering Transcultural Encounters Bodies, Image, and Frenchness in Latin America and North Africa - Navarro-Ayala, Luis (Palgrave Studies in Globalization and Embodiment,, 2019)
In a highly original and interdisciplinary work bridging French and Francophone studies, cultural studies, media studies, and gender and sexuality studies, Luis Navarro-Ayala examines the transnational queer body as a physical and symbolic entity intrinsically connected with space. Through a transcultural and intersectional approach to bodily representations, socioeconomic conditions, and postcolonial politics, Navarro-Ayala analyzes queerness and Frenchness in narratives from North Africa and Latin America, revealing that Frenchness is coded to represent a sexually deviant "Other." France and Frenchness, in two distinct regions of the global South, have come to represent an imagined queer space enabling sexual exploration, even in social conditions that would have otherwise prevented queer agency. .